ITSBAT NIKAH DECISIONS ISSUED BY THE RELIGIOUS COURTS OF CLASS 1A BENGKULU ON THE SPOUSES WHOSE ABSENCE IN MARRIAGE DOCUMENTS ACCORDING TO ISLAMIC MARRIAGE LAW - Kurniadi Agusta; Sirman Dahwal; Mohammad Darudin (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
In Bengkulu city, there is a marriage phenomenon done by the cultural law but not legally acknowledged in the data of ministry of religious office. Such a particular situation results in the absence of legal standing in terms of data. This being the case, spouses then ask for official marriage decisions or itsbat Nikah   to the office of ministry of religious so that they would receive marriage letter. To answer the problems, the method used is empirical law research method. Data are obtained through observation and interviews to informant judges, clerks and seekers of justice who apply for marriage. Furthermore, it is analyzed by qualitative juridical with deductive and inductive method, thus it can be drawn a conclusion to answer from every existing problem. The results of this study indicate that: 1) many spouses do not have a marriage document since they avoid sin due to adultery, and feel not ready materially and socially, become pregnant out of marriage, and are overwhelmed with the assumption that whether having marriage documents or not will be the same, 2) the legal consequences of marriage without a marriage certificate are considered invalid because such a marriage is illegal under the law No. 1/1974 stating that the wife also has no right to the livelihood and inheritance of the husband if he dies and is not entitled to, (3) the religious courts of Bengkulu states that it is important to issue the-so-called itsbat Nikah   or official documents to the spouses who have yet to legally declare their marriage as stated in the decree No.1/1974 for the betterment of the society.